(untitled) (The Review of Diabetic Studies, 2024)
Background: Physical inactivity among older adults poses a significant risk to public health, contributing to chronic illnesses and reduced quality of life. Public health nurses (PHNs), with their expertise in community engagement and preventive care, are well-positioned to lead physical activity (PA) interventions, particularly through community recreation centers. This study aimed to systematically review the evidence on the role and effectiveness of public health nurses in promoting physical activity among older adults through interventions delivered via community recreation centers. Methods: A systematic review was conducted using PRISMA guidelines. Databases including PubMed, Embase, Scopus, Web of Science, Cochrane Library, CINAHL, and PsycINFO were searched for studies published between January 2010 and January 2025. Eligible studies involved older adults (≥60 years), public health nurse-led PA interventions in community recreation settings, and reported PA-related outcomes. Twenty-five studies met inclusion criteria, ranging from pilot trials to randomized controlled trials. Results: PHNs led both direct and supportive interventions such as structured exercise programs, motivational interviewing, digital coaching, and behavioral counseling. Across most studies, interventions improved PA levels (e.g., step counts), blood pressure, BMI, functional mobility, quality of life, and self-efficacy. Nurse-led programs showed high acceptability, feasibility, and low adverse event rates. Technological tools (e.g., wearable trackers, web-based platforms) enhanced scalability but showed mixed acceptability among older users. Conclusion: PHNs play a pivotal role in promoting physical activity among older adults through tailored, accessible, and community-based approaches. Their interventions demonstrate improved health outcomes and engagement, highlighting their importance in public health strategies targeting aging populations.